Preparation of activated carbons from fruit residues for the removal of naproxen (NPX): analytical interpretation via statistical physical model (2022)
In this work, physical statistical models were employed to provide reasonable information regarding the adsorption of naproxen onto different activated carbons. The activated carbons were prepared from different biomasses (pitaya peels, jabuticaba peels, or grape residues from the winery process) using ZnCl2 as an activator. All the adsorbents were characterized regarding their functional groups and morphological surfaces. The maximum capacity obtained for the activated carbons (at 328 K) was found to be: 167.0 mg g−1 for jabuticaba peels at pH 4; 158.81 mg g−1 for pitaya peels at pH 6.7; and last., grape residues the capacity was 176.0 mg g−1 at pH 7. The equilibrium data of the three adsorbents were well fitted to the monolayer with two energy sites adsorption model, assuming that NPX adsorption on the carbon surfaces occurs via two different functional groups. This statistical physics model calculated the number of NPX molecules bound on the surface and the saturated adsorption capacity for both functional groups at different temperatures. The obtained results indicate that the naproxen molecules can be adsorbed in a parallel and horizontal manner according to the material employed. The receptor density tends to increase with the temperature evolution, indicating that thermal energy and solubility play an important role in adsorption. Configurational entropy indicates similar thermodynamic behavior for all materials where higher disorder is found at the early stages of the adsorption, followed by and decrease a possible organization of the molecules on the surface. The Gibbs free energy shows that adsorption of naproxen is spontaneous in all cases and internal energy is proportional to the adsorption capacity indicating that the system releases energy as the adsorption occurs. Therefore, this article reports new findings to understand the adsorption mechanism of naproxen molecules on activated carbons prepared from lignocellulosic biomass.